2012
DOI: 10.1002/jcb.24210
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia modulation of peroxisome proliferator‐activated receptors (PPARs) in human glioblastoma stem cells. Implications for therapy

Abstract: Gliobastoma (GB), the most common adult brain tumor, infiltrates normal brain area rendering impossible the complete surgical resection, resulting in a poor median survival (14-15 months), despite the aggressive multimodality treatments post-surgery, such as radiation and chemo-therapy. GB is characterized by hypoxic and necrotic regions due to a poorly organized tumor vascularization, leading to inadequate blood supply and consequently to hypoxic and necrotic areas. We have previously shown that, under hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…We previously demonstrated that HIF1α is a TNFα target [12]. Moreover, literature data report that HIF1α is a potential PPARα target [33]. Here, we observed that exposure of MCF7-MS and MCF10-MS to the TAF supernatant elicited HIF1α transcriptional activity (Figure 2C) and mRNA expression (+65%, p <0.05, in MCF10-MS; +76%, p <0.01, in MCF7-MS, Figure S2A).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…We previously demonstrated that HIF1α is a TNFα target [12]. Moreover, literature data report that HIF1α is a potential PPARα target [33]. Here, we observed that exposure of MCF7-MS and MCF10-MS to the TAF supernatant elicited HIF1α transcriptional activity (Figure 2C) and mRNA expression (+65%, p <0.05, in MCF10-MS; +76%, p <0.01, in MCF7-MS, Figure S2A).…”
Section: Resultssupporting
confidence: 64%
“…Noteworthy, PPARγ plays a significant inhibitory role on the inflammatory process [30][31], while PPARα exerts pro-inflammatory activity [32]. Interestingly, the expression of PPARα increases, while that of PPARγ decreases in neural stem cells exposed to hypoxia [33]. In this study, MS from normal (N-MS) and tumor (T-MS) tissues, as well as from tumorigenic MCF7 (MCF7-MS) and non tumorigenic (MCF10-MS) human breast cell lines, were exposed to the supernatant of normal mammary gland and breast tumor associated fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether this HIF-1α–PPAR pathway occurs in cancer cells remains unclear ( Figure 2 , route 16). In cancer, PPARα is upregulated at the transcriptional level in response to hypoxia in GBM cells [ 109 , 110 ]. This PPARα activation is associated with increased HIF-1α expression, number of peroxisomes, and LD levels [ 109 , 110 ].…”
Section: Molecular Mechanisms Associated With the Biosynthesis Of mentioning
confidence: 99%
“…In cancer, PPARα is upregulated at the transcriptional level in response to hypoxia in GBM cells [ 109 , 110 ]. This PPARα activation is associated with increased HIF-1α expression, number of peroxisomes, and LD levels [ 109 , 110 ]. The lipid components of LDs, including TAG and cholesterols, are increased in GBM cells in response to hypoxia [ 109 , 110 ].…”
Section: Molecular Mechanisms Associated With the Biosynthesis Of mentioning
confidence: 99%
“…PPAR activity is involved in osteoblastic differentiation (Takano et al, 2012) and hypoxia modulation of HIF1a and PPARs in human glioblastoma stems cells (Galzio et al, 2012). Evidence has also suggested that ING1b negatively regulates HIF1a protein levels in adipose-derived stromal cells in a SUMOylation-dependent mechanism (Bigot et al, 2015).…”
Section: Ing1b Regulates the Expression Of Ppar-b/d In Mc3t3-e1 Cellsmentioning
confidence: 99%